(Be)Come Entrepreneur: Process of Creating and Adapting Business During the Pandemic (Management and Connections Journal, 2024)
The aim of this study was to understand the complexities of becoming an entrepreneur during the COVID-19 pandemic. To this end, seven entrepreneurs in the area of ​​services, self-employed professionals and self-employed businesses were interviewed about ‘becoming’ and ‘being an entrepreneur’ during the pandemic. The interview reports were transcribed and analyzed using content analysis. The results showed the process of 'becoming' and 'being an entrepreneur' in an interconnected way throughout the pandemic process, allowing the emergence of a new category of analysis of the entrepreneurial process: becoming + being an entrepreneur – tornar-se(r). Becoming + being an entrepreneur – tornar-se(r) presents itself as an adaptive resource for entrepreneurs to deal with the contextual changes arising from the pandemic, which requires entrepreneurs to constantly reinvent their own business through adaptive strategies that 'become' and make them 'being' new entrepreneurs as health protocols, social norms and economic interventions are exercised throughout the pandemic.
Keywords: Entrepreneurship; Process; Pandemic; Work; Career